Correspondance générale d'Helvétius, Volume V : Appendices et Index - Helvetius, 1715-1771 (Book collections on Project MUSE., 2004)
This fifth and final volume completes the critical edition of the letters of French philosopher Claude Adrien Helvetius (1715-1771), author of the controversial De l'Esprit (1758), and of his wife, nee Anne Catherine de Ligniville (1722-1800), who ran her own salon in Auteuil after her husband's death. The essential component in this last volume is the detailed index - an indispensable instrument for researchers who wish to make full use of the correspondence. The volume also includes four new letters discovered since the appearance of the first four volumes, errata, additions and modifications to the critical apparatus, the text of letters excluded from the edition proper, genealogies of the families of Helvetius and his wife, and a chronological list of all letters mentioned in the edition.